The zoom : drama at the touch of a lever - Hall, Nick, 1985- (Techniques of the moving image., 2018)
From the queasy zooms in Alfred Hitchcock's Vertigo to the avant-garde mystery of Michael Snow's Wavelength, from the excitement of televised baseball to the drama of the political convention, the zoom shot is instantly recognizable and highly controversial. Nick Hall traces the century-spanning history of the zoom lens in American film and television.